The effect of job satisfaction on employee commitment - Maria Dalkrani; Efstathios Dimitriadis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2019)
Purpose: This study examines the degree of employee satisfaction from the different factors that theoretically affect satisfaction. Moreover, the relationship between the factors of job satisfaction and organizational commitment on private employees is examined. Design/methodology/approach: In order to achieve the objectives of this study, the survey was conducted using a structured questionnaire in January and March 2018. The final sample size consists of 439 private employees in Greece. The most frequent questioned industry is services, followed by trade and manufacturing at a smaller rate. The research instrument for content and construct validity was tested. Data were analyzed using ANOVA, Correlation and Regression analysis. Findings: The results showed that the 'Social Aspects of job', 'Job Characteristics' and 'Work Environment', are the most important factors positively affecting organizational commitment, while "Promotion" and "Rewards" are not significant factors. Research limitations/implications: During survey some limitations were found to exist, the largest being the small sample size. Additionally, subjective measures of employee satisfaction were used instead of objective measures. However, this study shows that job satisfaction is inherently interwoven with organizational commitment. Since organizational commitment has a direct impact on employee retention, performance, and organizational behavior, it is essential to meet the required conditions for its existence Originality/value: In the recent years of Greek economic crisis, very few private sector studies have addressed the satisfaction of employees and their commitment to the organization.
Keywords: M12; 330; Job Satisfaction; Organizational; Commitment; Private Employees; Greek Organizations